Penilaian Resiko Musculoskeletal Disorders Pekerja Harian Lepas PDAM Tirta Lawu Karanganyar - Fiko Erisa Fatq; Irwan Iftadi; Yuniaristanto - (Industrial Engineering Study Program, Faculty of Engineering, Universitas Sebelas Maret, 2014)
PDAM Tirta Lawu Karanganyar is a local company that handles the distribution of water inKaranganyar, Central Java. The company serves the whole society of the various groups. In the process of delivery service, it was found the existence of Manual Material Handling (MMH) in the installation of water distribution networks. There are some activities which relatively easy to do, but in time and high repetition. In the beginning of interview was found that 4 from 6 workers have back pain in the hips and waist after work, then the part of body will be mapped by Nordic Body Map as a tool to strengthen the notion of mapping. This study uses REBA as the most appropriate valuation method in proving the existence of Musculoskeletal Disorders (MSDs) in the workplace. The result is there are 5 work elements as a subject of ergonomics evaluation. REBA method was proved to show some activities on high risk for the operator health of non-permanent employees (PHL)